A NEW PHENOLIC COMPOUND FROM ACETONE EXTRACT OF LICHEN Usnea flexuosa Tayl. - Maulidiyah Maulidiyah; A. Herry Cahyana; Wahyudi Priyono Suwarso (Universitas Gadjah Mada, 2011)
Natural product, 2'-hydroxy-1'-(4-hydroxyl-5-methoxy-2-methyl-phenyl)-ethanon, (1), was isolated from the thalli lichen Usnea flexuosa Tayl. together with the known (-) - usnic acid (2). The structure of compounds 1 and 2 were determined by the spectroscopic studies.